2023
DOI: 10.1101/2023.02.08.527777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic profiles of stress susceptibility and resilience in the amygdala and hippocampus

Abstract: A single, severe episode of stress can bring about myriad responses amongst individuals, ranging from cognitive enhancement to debilitating and persistent anxiety; however, the biological mechanisms that contribute to resilience versus susceptibility to stress are poorly understood. The dentate gyrus (DG) of the hippocampus and the basolateral nucleus of the amygdala (BLA) are key limbic regions that are susceptible to the neural and hormonal effects of stress. Previous work has also shown that these regions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…While its involvement in stress susceptibility is well-documented, the amygdala's role in stress resilience remains less clear. For instance, in a rodent study, it was found that, unlike the hippocampus, which played a role in both stress vulnerability and resilience, the amygdala was primarily associated with stress vulnerability ( Long et al, 2023 ). Similar results had been observed in human cohorts, where the amygdala and its associated connectivity network were linked to stress responses during the COVID-19 pandemic but did not demonstrate the same significance in stress resilience ( Zhou et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While its involvement in stress susceptibility is well-documented, the amygdala's role in stress resilience remains less clear. For instance, in a rodent study, it was found that, unlike the hippocampus, which played a role in both stress vulnerability and resilience, the amygdala was primarily associated with stress vulnerability ( Long et al, 2023 ). Similar results had been observed in human cohorts, where the amygdala and its associated connectivity network were linked to stress responses during the COVID-19 pandemic but did not demonstrate the same significance in stress resilience ( Zhou et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, many individuals possess the capacity to adapt to stressors and employ adaptive responses, showing resilience (Franklin, Saab et al 2012; van der Werff et al, 2013 ). Investigating the neurobiological mechanisms underlying both stress susceptibility and resilience contributes to a deeper understanding of the processes involved in stress-related disorders and might pave the way for new approaches to the prevention and treatment of these conditions ( Charney 2004 , Long et al, 2023 ).…”
Section: Instructionmentioning
confidence: 99%
See 1 more Smart Citation